Last Mile Delivery with Parcel Lockers: evaluating the environmental impact of eco-conscious consumer behavior. Issue 5 (2022) - Bonomi, V.; Mansini, R.; Zanotti, R.
Abstract: In recent months, online sales have experienced a sharp surge also due to the COVID pandemic. In this paper, we propose a new location and routing problem for a last mile delivery service based on parcel lockers and introduce a mathematical formulation to solve it by means of a MIP solver (Gurobi). The presence of parcel locker stations avoids the door-to-door delivery by companies but requires that consumers move from home to collect their parcels. Potential location of locker stations is known but not all of them need to be opened. The problem minimizes the global environmental impact in terms of distances traveled by both the delivery company and the consumers deciding the optimal number of stations that have to be opened. How much do the number and location of lockers impact on environment? Is the behavior of consumers a critical aspect of such optimization? To this aim we have solved 1680 instances and analyzed diferent scenarios varying the number of consumers and potential parcel lockers, the maximum distance a consumer is willing to travel to reach a locker station, and the maximum distance we may assume the same consumer is willing to travel by foot or by bicycle. The experimental results draw interesting conclusions and managerial insights providing important rules of thumbs for environmental decision makers.